2018
DOI: 10.1038/s41592-018-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

SAVER: gene expression recovery for single-cell RNA sequencing

Abstract: In single-cell RNA sequencing (scRNA-seq) studies, only a small fraction of the transcripts present in each cell are sequenced. This leads to unreliable quantification of genes with low or moderate expression, which hinders downstream analysis. To address this challenge, we developed SAVER (single-cell analysis via expression recovery), an expression recovery method for unique molecule index (UMI)-based scRNA-seq data that borrows information across genes and cells to provide accurate expression estimates for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
674
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 647 publications
(679 citation statements)
references
References 29 publications
5
674
0
Order By: Relevance
“…We assume that the single cell expression level of a given gene follows the negative binomial distribution, which also arises as a continuous mixture of Poisson distributions with the gamma-distributed Poisson rate. Huang et al 14…”
Section: Parameterization Of Gene Expression Distribution Of Single Cmentioning
confidence: 99%
“…We assume that the single cell expression level of a given gene follows the negative binomial distribution, which also arises as a continuous mixture of Poisson distributions with the gamma-distributed Poisson rate. Huang et al 14…”
Section: Parameterization Of Gene Expression Distribution Of Single Cmentioning
confidence: 99%
“…For droplet datasets, the observed UMI count can be modeled as a NB random variable, which also arises as a Poisson-gamma mixture 35 :…”
Section: Expression Entropy Modelmentioning
confidence: 99%
“…The and are shape parameter and rate parameter respectively. Given the assumption that the shape parameter is a constant across cells and genes, and that the rate parameter is a constant of gene across cells 35,36 , and can be expressed as and , respectively. Then the distributions can be recognized as:…”
Section: Expression Entropy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that batch effects account for a substantial percentage of dropout variability at the cell level [1]. Many imputation methods have been proposed in recent years to recover dropouts [18,[21][22][23][24] in scRNA-seq data. However, among these methods, only BUSseq [18] takes both batch effects and dropout events into consideration.…”
Section: Introductionmentioning
confidence: 99%